Effect of COVID-19 on Mental Health of Health Workers in Malawi (Policy Brief) - Kainja, Jimmy; Maliwichi, Limbika; Kondowe, Fiskani; M'manga, Chilungamo; Nyamali, Simunye; Mchenga, Martina; Ndasauka, Yamikani (My University, 2024)
Mental health or psychological well-being is integral to an individual's capacity to lead a fulfilling life, including forming and maintaining relationships, studying, working, or pursuing leisure interests and making day-to-day decisions about these issues. Disturbances to a person's mental well-being can adversely compromise their capacity to make the right choices, leading to diminished functioning at the individual level and broader welfare losses for one's household and society. A recent analysis by the World Economic Forum estimated that the cumulative global impact of mental disorders in terms of lost economic output would amount to US$ 16 trillion over the next 20 years. The estimate marks mental health as a significant concern for public health, economic development, and societal welfare. The current study by Covid-19 and Mental Health in Malawi project has also highlighted the importance of mental health and the effects of neglecting it.
Keywords: COVID-19; Malawi; Mental Health; Mental Health Workers